PENGARUH KARAKTERISTIK INDIVIDU, ORIENTASI KERJA, DAN PENEMPATAN PEGAWAI TERHADAP KINERJA PEGAWAI PADA DINAS PERTANIAN DAN PANGAN KABUPATEN BADUNG - Ni Kadek Sukma Dwijayanti; A.A.Dwi Widyani; Daniel Manek (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2022)
Employee performance problems are known on the working time indicator. This is because employees have not been able to do a good job. Employees feel that their current work abilities are not commensurate with the demands of the job. The office is not able to provide a warm welcome in the form of friendliness to new employees. The low attitude of employees in accepting work responsibilities, so that many jobs are neglected and not completed on time. This study aims to determine the effect of individual characteristics, work orientation and employee placement on employee performance at the Badung Regency Agriculture and Food Office. This research was conducted at the Department of Agriculture and Food of Badung Regency using a population and a sample of 45 employees. The sampling technique used is the saturated sampling method or the census method. Data was collected through documentation, interviews and questionnaires. The data analysis technique used is multiple linear regression analysis which is processed using Statistical Package for Sosial Science (SPSS) relase version 25 for windows. Based on the results of the analysis, this study shows that individual characteristics, work orientation and employee placement partially have a positive and significant effect on employee performance at the Agriculture and Food Office of Badung Regency.